1974
DOI: 10.1002/pssa.2210240119
|View full text |Cite
|
Sign up to set email alerts
|

Auger recombination in germanium

Abstract: The rate for electron‐hole hole Auger recombination in germanium has been recalculated by taking into account the detailed band structure including valence band splitting, nonparabolicity of the valence bands, and the influence of Γ‐point conduction band minimum. The transition matrix elements were calculated with the aid of the k · p approximation method, using optical data obtained from the fundamental direct absorption and from the inter‐valence band absorption. The value obtained for the recombination coef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1975
1975
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Therefore, we have exact results for all these processes so that the uncertainties are removed which are contained Auger Coefficients for III-V Semiconductors with Emphasis on GaSb (4), the usefulness of the k . p-perturbation approximation (6) and the validity of the screening terms (5).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we have exact results for all these processes so that the uncertainties are removed which are contained Auger Coefficients for III-V Semiconductors with Emphasis on GaSb (4), the usefulness of the k . p-perturbation approximation (6) and the validity of the screening terms (5).…”
Section: Discussionmentioning
confidence: 99%
“…The quadratic carrier density dependence implicates that Auger recombination becomes a dominant loss mechanism at high-charge carrier densities, which can be the order of >10 19 cm −3 for typical laser devices. Extensive theoretical work based on perturbation theory has shown that, despite its indirect band gap, the band structure of both, Si and Ge, is favorable for direct Auger recombination (Huldt, 1974;Lochmann, 1978) . This is comparable to direct band gap materials like GaAs or GaN used for optical devices in the visible part of the spectrum but still much smaller than for low band gap materials like InAs (Metzger et al, 2001).…”
Section: Auger Recombinationmentioning
confidence: 99%
“…However, in the early phases of decay (i.e., first 75 psec), the kinetics is dominated by the Auger recombination, and is independent of diffusion to first order. More specifically the initial decay rate is (2) for the case of an exponential spatial distribution n(z, 0) = n 0 e ~a z , under the assumption that the crystal thickness L is much greater than the pump absorption depth, a" 1 . The value of the initial decay rate is shown as a dotted line in Fig.…”
mentioning
confidence: 99%